The heuristic preemptive dispatching method for convey-based automated material handling system of 450 mm wafer fabrication. (June 2016) - Wang, Chia-Nan; Lee, Yueh-Hsiu; Hsu, Hsien-Pin; Nguyen, Dinh-Hiep
Highlights: The 450 mm wafer fabrication is the current trend of semiconductor industry. Conveyor-based automated material handling system (AMHS) has been suggested. A heuristic preemptive dispatching method is proposed for a convey-based AMHS. The AMHS is restructured based on activated roller belt (ARB). Experimental results show the proposed preemptive dispatching method is effective. Abstract: The 450 mm transition of wafer fabrication is the current trend of semiconductor industry. However, the increased size and weight of wafers pose challenges on wafer handling and transportation. To address this issue, conveyor-based automated material handling system (AMHS) has been suggested as a solution due to its advantages. However, the lack of an effective and efficient dispatching method will make a convey-based AMHS to remain suffer traffic-jams problem and short the capability to handle hot lots to meet customer needs. In this study, a heuristic preemptive dispatching method (HPDB) is proposed for controlling the movements of wafer lots in a convey-based AMHS that is restructured based on activated roller belt (ARB) and to be used for 450 mm wafer fabrication. To investigate the effectiveness of the HPDB, simulation experiments have been conducted and the results obtained from HPDB has been compared to that obtained from HPD. The experimental results show that HPDB outperforms HPD in terms of average delivery time, with the advantages of 55.11% for hot lots and 55.76% for normal lots. This indicates that HPDB can better solve the traffic-jam problem and reduce transportation time.